Effects of prehospital advanced airway management on cardiac arrest patients who underwent extracorporeal cardiopulmonary resuscitation - Naoki Kawahara; Wataru Takayama; Koji Morishita; Yasuhiro Otomo; Akihiko Inoue; Toru Hifumi; Tetsuya Sakamoto; Yasuhiro Kuroda (Scientific Reports)
Abstract The effect of prehospital advanced airway management (AAM) in patients with out-of-hospital cardiac arrest requiring extracorporeal cardiopulmonary resuscitation remains unclear. In this retrospective study, we analysed data from the Study of Advanced Cardiac Life Support for Ventricular Fibrillation with Extracorporeal Circulation in Japan II, encompassing 36 institutions in Japan (2013–2018). Patients were divided into two groups: those who received prehospital AAM and those who did not. The primary outcome was a favourable neurological outcome at discharge, and secondary outcomes included 30-day survival, estimated low-flow time, duration of mechanical ventilation, and length of stay in the intensive care unit. A generalised estimating equation model adjusted for prehospital confounders was used for between-group comparisons. Sensitivity analysis was performed using propensity score matching. Among 1,789 patients, those who received prehospital AAM had significantly lower favourable neurological outcomes at discharge, lower 30-day survival, longer low-flow time, shorter mechanical ventilation days, and shorter intensive care unit stay days than those who did not receive prehospital AAM. Propensity score-matched analysis confirmed these findings. Prehospital AAM in patients with out-of-hospital cardiac arrest undergoing extracorporeal cardiopulmonary resuscitation was associated with poorer clinical outcomes. Further studies are needed to optimise prehospital care for these patients.